A comprehensive functional classification of cleft hand: The DAST concept - Alok Sharma; Namita Sharma (Indian Journal of Plastic Surgery)
Context: Phenotypic expressions of the congenital cleft hand are variable and might baffle even the experienced as to the choice of surgery. The morphological parameters defining the anomaly dictate not only the functional capacity of the anomalous hand but also the degree of possible surgical restoration. Despite a large number of classifying systems available, none encompass all the relevant issues. Aims: The purpose of this work is to present an all-inclusive and universally acceptable classification of the deformity which would graphically represent the entire gamut of possible presentations; principal and associated. Furthermore, based on such staging, the choice of surgical procedure and the stages of surgical intervention can be standardised to ensure the best results for the patient. Patients and Methods: This study is based on a series of 27 patients with a total of 38 cleft hands. Results and Conclusions: The necessity to include and to assess all determinants of function and complexity in these hands to standardise the choice of management, gave rise to the DAST system of classification; an acronym for all the morphological determinants of the anomaly (D = Digits missing, A = Associated anomalies in the hand, S = Site of cleft, T = Functional state of the Thumb). Numerical values were assigned to each component in increasing order of complexity. Score for each determinant as well as the aggregate score indicates the degree of complexity in a graphic manner. The DAST classification has a predictive value in choice of procedure and prognosticating surgical outcomes.